2006
DOI: 10.1002/ejoc.200600675
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a 2D Lander

Abstract: A method for the preparation of an asymmetric superbenzene is presented. The synthesis proceeds through the 12-fold cyclodehydrogenation of a polyaromatic precursor obtained by successive Diels-Alder additions of cyclopentadienones and alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Starting diynes 1a ,19 1b ,19 1c ,20 1d ,18 1e ,19 1f ,21 1g ,19 1h ,19 1i ,19 1j ,22 1k ,21 1l ,22 1m ,23 1n ,24,25 1o ,26 1p ,27 and 1q 22 were prepared according to the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Starting diynes 1a ,19 1b ,19 1c ,20 1d ,18 1e ,19 1f ,21 1g ,19 1h ,19 1i ,19 1j ,22 1k ,21 1l ,22 1m ,23 1n ,24,25 1o ,26 1p ,27 and 1q 22 were prepared according to the literature.…”
Section: Methodsmentioning
confidence: 99%
“…The reactions of the diyne 249 with various nitriles containing methyl, ethyl, vinyl, phenyl, hydroxyl, and carboxy groups proceeded in moderate to quantitative yields when conducted with 10 mol‐% of CpCo(CO) 2 catalyst in toluene under microwave irradiation for 10–20 min affording the desired azatriphenylenes 251 . The precursor diyne 249 was synthesized according to the previously reported method starting from (2′‐hydroxymethylbiphenyl‐2‐yl)methanol . This new azatriphenylene synthesis enabled the efficient assembly of the penta‐cyclic phenanthroindolizidine alkaloids dehydrotylophorine ( 1 ) and tylophorine ( 2 ).…”
Section: Synthetic Approaches Towards Azatriphenylene Derivatives:mentioning
confidence: 99%
“…The synthesis was commenced with the commercially available iodobenzene 252 which is selectively dimerized by the treatment with phenyliodine bis(trifluoroacetate) (PIFA) to give 253 in 84 % yield. A three‐step conversion via a Corey–Fuchs reaction was employed for the transformation of 253 into 255 . After synthesizing the diyne ( 255 ), it was treated with a cyano mesylate ( 256 ) to perform microwave‐mediated [2+2+2] cyclotrimerization reaction under cobalt catalysis in 20 min (Scheme ).…”
Section: Synthetic Approaches Towards Azatriphenylene Derivatives:mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Applications of these building block molecules have been extended to the generation of acetylene derivatives, including alkynylphosphonates, [6] ynol ethers, [7] symmetric and asymmetric 1,3-diynes, [8] ynamides, [9] 1,2-diarylacetylenes, [10] ynoate esters, [11] and ynsilanes. [12] Piguel et al proposed a method for copper-catalyzed, C 2 -directed alkynylation of 3H-imidazo [4,5-b]pyridine derivatives using 1,1-dibromo-1-alkenes. [13] Bach et al reported the synthesis of propynamides by utilizing gem-dibromoalkenes and isocyanate under harsh, multi-step condi-tions, [14] whereas Xu et al established a process for the selective synthesis of 1,2-heterodisubstituted alkenes via nucleophilic b-addition to gem-dibromoalkenes followed by a cross-coupling reaction.…”
Section: Introductionmentioning
confidence: 99%